Paraguay : First Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance and Applicability of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2004)
This paper assesses Paraguay's First Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance and Applicability of Performance Criteria. Paraguay has made significant progress in the first months of the program. Economic activity has strengthened, inflation prospects have improved, and renewed confidence in economic policy management has helped boost banking system deposits and central bank reserves. Fiscal performance has been favorable, but continued reforms are needed to keep the program on track. The IMF staff welcomes the authorities' efforts to address Paraguay's payments arrears difficulties.